Research on the Association Between Obstructive Sleep Apnea Hypopnea Syndrome Complicated With Coronary Heart Disease and Inflammatory Factors, Glycolipid Metabolism, Obesity, and Insulin Resistance - Wen, Yumei; Zhang, Haibin; Tang, Yu; Yan, Rui (Frontiers in Endocrinology, 2022)
The study aimed to explore the association of whether obstructive sleep apnea hypopnea syndrome (OSAHS) is complicated with coronary heart disease (CHD) with the inflammatory factors, glycolipid metabolism, obesity and insulin resistance. 400 patients diagnosed with OSAHS underwent polysomnography (PSG) monitoring in the Sleep Diagnosis and Treatment Center of Beijing Luhe Hospital from March 2015 to September 2018 were selected and divided into OSAHS group (n=200) and OSAHS + CHD group (n=200) according to the condition of disease. The questionnaire survey was conducted, the somatology indexes were measured, and the PSG, insulin, glycolipid metabolism parameters and serum inflammatory factors were detected. The body weight, body mass index, waist circumference and Epworth sleepiness scale (ESS) score were all significantly increased in OSAHS + CHD group compared with those in OSAHS group (p<0.05). The microarousal index (MAI), apnea hypopnea index (AHI), cumulative percentage of time spent at oxygen saturation below 90% (CT90%), oxygen desaturation index (ODI), lowest oxygen saturation (LSaO2), total apnea time (TAT) and mean oxygen saturation (MSaO2) had statistically significant differences between OSAHS + CHD group and OSAHS group (p<0.05). According to the Spearman correlation analysis of AHI, LSaO2, MSaO2, CT90%, ODI and MAI with HOMA-IR in both groups, MAI, AHI, CT90% and ODI were positively correlated with HOMA-IR (r>0), while LSaO2 and MSaO2 were negatively correlated with HOMA-IR (r<0). Compared with OSAHS group, OSAHS + CHD group had an obviously increased level of triglyceride (TG) (p<0.05), and obviously increased levels of serum inflammatory factors C-reactive protein (CRP), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and interferon-γ (IFN-γ) (p<0.05).The occurrence of OSAHS complicated with CHD is related to the inflammatory factors, glycolipid metabolism, obesity rate and HOMA-IR.